ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA INDUSTRI PERBANKAN DENGAN VARIABEL MODERATING KEPEMILIKAN MANAJERIAL ( Studi Empiris pada Periode Sebelum dan Sesudah Implementasi IFRS di Indonesia ) - Muhamad Arief Sandy N; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This research seeks to study the effect of implementation of IFRS to practice of earnings management through Loss Loan Provisions (LLP). The study also examined whether moderating effect of managerial ownership on earnings management loss loan provisions. The object of research used in this study is a banking company listed on the Stock Exchange 2008-2012 period. The variabels studied were measured with LLP earnings management as a proxy for income smoothing. The analysis technique used in this research is multiple linear regression. The results of this study showed existing positive effect of the Loan Charge-offs (LCO), Loan Loss Allowance (LLA), Non Performing Loan (ΔNPL), and Earnings Before Tax and Provisions (EBTP) against LLP the banking company both before and after adoption IFRS. In addition, managerial ownership variabel does not moderate the effect of earnings management on the loss loan provisions.